S70 Experimental Human Pneumococcal Colonisation is an asymptomatic event in healthy adults. (12th November 2015) - Trimble, A; Collins, AM; Hancock, CA; Gordon, SB; Ferreira, DM; Wright, AD
Abstract : Background: Pneumococcal colonisation is a necessary precursor for pneumococcal diseases. Previous studies have suggested that pneumococcal colonisation in children is symptomatic and that there is a relationship between symptom severity/frequency and colonisation density. The literature refers to colonisation in adults as an asymptomatic event but no studies have used robust methodology. Using the Experimental Human Pneumococcal Colonisation (EHPC) model, we investigated whether pneumococcal colonisation (or co-colonisation with a respiratory virus) is symptomatic in healthy adults. Methods: Non-smoking healthy adults aged 18–60 years old were recruited and inoculated intranasally with 0.1 ml per naris of pneumococcus (serotype 6B, 23F) or saline (control). Nasal and non-nasal symptoms were monitored pre-inoculation and for 7 days post-inoculation using a modified Likert score. Symptom severity scoring ranged from 1 (none) to 7 (cannot function). Area under the curve (AUC) was calculated for each participant. Mean values were compared using ANOVA between the groups. Results: Data from 53 participants were analysed. 45 were inoculated with pneumococcus and 8 with saline. In total, 14 became experimentally colonised. Colonised and non-colonised participants reported similar symptom severity scores (Figure 1 ). Mean severity scores for both nasal and non-nasal symptoms did not significantly differ according to colonisation status (p > 0.05), nor was there any significant association with any particular symptom. In the 14 experimentally colonised participants, density of colonisation did not correlate with symptom severity scores (R 2 = 0.03, p = 0.89). 6 participants were co-colonised (with pneumococcus and a respiratory virus), although they showed a trend towards experiencing more non-nasal symptoms than other groups, their mean symptom severity was still occasional only (p > 0.05). Conclusion: In healthy adults pneumococcal colonisation is an asymptomatic event, regardless of density or viral co-colonisation.